Communication Model of Real-time Interactive Avatar: Virtual Public Figure - Sabeth Uttara; Betha Almanfaluthi (International Journal of Educational Technology and Artificial Intelligence, 2023)
This paper discusses the widespread use of avatars beyond gaming, which has led to significant changes in the entertainment industry with the emergence of various virtual public figures. Avatars have evolved beyond static forms or limited movements and can now interact with users in a more human-like manner. The author utilizes a self-designed avatar named Crystagella to showcase the potential of avatars as a medium for communication beyond their current applications. To address communication issues between actors, avatars, and audiences, the author employs the design thinking method, resulting in innovation in real-time interaction schematic modeling with avatars. This study provides valuable insights into the potential applications of avatars in various fields, including entertainment, education, and virtual reality. It also highlights the significance of motion capture technology in creating lifelike avatars, with an emphasis on the importance of low latency and detail-oriented motion capture. Overall, this paper contributes to the growing body of research on avatars and their potential in modern communication. The insights gained from this study can serve as a basis for the development of advanced interaction modeling and the design of more intuitive and effective avatar communication tools in the future.